Intracameral mydriatics in phacoemulsification cataract surgery – a 6‐year follow‐up. (9th March 2012) - Lundberg, Björn; Behndig, Anders
Abstract. Purpose: To evaluate the long‐term safety of intracameral mydriatics (ICM) in phacoemulsification cataract surgery compared with conventional topical mydriatics (TM). Methods: A total of 45 patients were examined 6 years after phacoemulsification cataract surgery. The patients had previously participated in a prospective randomized double‐blind study including 60 patients, operated with either ICM or TM. The follow‐up included best‐corrected visual acuity (BCVA), intraocular pressure (IOP), grade of posterior capsule opacification (PCO), YAG laser capsulotomy rate, pupil size, corneal thickness and endothelial morphology. Results: No differences in postoperative BCVA, IOP, pupil size, PCO or YAG rate were observed between the groups. Endothelial cell loss, endothelial morphology and corneal thickness were also equivalent. Conclusions: Intracameral mydriatics is a safe alternative to topical mydriatics in phacoemulsification cataract surgery with no long‐term disadvantages at 6‐year follow‐up.